Phenotypic markers of syndrome of unspecified connective tissue dysplasia in children with acquired myopia (Ukrainian Journal of Ophthalmology, 2026)
Background: Myopia can be caused by structural and functional alterations in the connective tissue.Purpose: To evaluate the phenotypic markers of the syndrome of unspecified connective tissue dysplasia (SUCTD) in a cohort of children with acquired myopia.Materials and Methods: Two hundred and thirty 7-15-year-old children with acquired myopia of low or moderate degree were involved in the study. They were divided into two age groups, junior (7-11 years; 102 individuals) and senior school children (12-15 years; 128 individuals). Odds ratios (OR) and 95% confidence intervals (CI) were used to assess the risk of myopia progression.Results: The major phenotypic risk factors for developing moderate myopia in children of 7-11 years were prominent venous network of the skin (OR, 7.8; 95% CI, 2.9-20.7; p < 0.05), asthenic habitus (OR, 4.9; 95% CI, 2.1-11.8; p < 0.05), and flat foot (OR, 4.0; 95% CI, 1.7-9.5; p < 0.05), whereas in children of 12-15 years, these factors were moderate or severe connective tissue dysplasia (OR, 7.9; 95% CI, 3.2-19.3; p < 0.05), asthenic habitus (OR, 7.1; 95% CI, 3.2-15.7), cardiac valve prolapse and other minor cardiac anomalies (OR, 6.9; 95% CI, 3.1-15.3; p < 0.05),  hypermobility of the joints (OR, 6.1; 95% CI, 2.7-13.6; p < 0.05), postural anomalies and scoliosis (OR, 5.6; 95% CI, 2.5-12.4; p < 0.05), and hyperelasticity of the skin (OR, 5.3; 95% CI, 2.3-12.5; p < 0.05).Conclusions: Low myopic children with a moderate or severe connective tissue dysplasia are at risk for developing moderate myopia. The major SUCTD-related risk factors for developing moderate myopia in children of 7-11 years were prominent venous network of the skin, asthenic habitus, and flat foot, whereas in children of 12-15 years, these factors were asthenic habitus, cardiac valve prolapse and other minor cardiac anomalies,  hypermobility of the joints, postural anomalies and scoliosis, and hyperelasticity of the skin.
Keywords: children; myopia; connective tissue dysplasia